RAPE, JUSTICE AND GENDER A MULTIDIMENSIONAL APPROACH OF AN HISTORICAL VIOLENCE (LA MATANZA, BUENOS AIRES, 18th CENTURY) - Quarleri, Lia (Revista de Historia Social y de las Mentalidades, 2021)
This work focuses on studying the judicial process deployed in Buenos Aires after the violation denounced by Bernabela Franco, in 1778. The judicial process happened days after being attacked by a male neighbor at her home in La Matanza, being her husband absent. This analysis preceded by a question: in what dimensions was the violence of rape expressed in that particular context? These dimensions will repair in the sentences, the configuration of the crime, the terminologies used, the gender imaginary, and her perceptions of the damage. We consider that the violence of rape is multidimensional. It produced socio-emotional traumas linked to the fact, social signaling, and judicial scrutiny, which occurred after the complaint.